The protect mobile user data in Russia - Anna Zharova (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper studies the issue the information security for smartphone users in Russia. The report analyses the regulations the state uses to prevent undeclared functionality and malicious programs in mobile phones in Russia; the law enforcement practice in this area; the responsibility of legal entities, officials and persons for non-compliance with the requirements for standardization, ensuring information security and violation of declaration of conformity. The paper develops proposals to improve state regulation of undeclared functionality of mobile devices providing the collection of information, including confidential data. The report discusses specific ethical issues related to privacy, including matters relating to compensation for damage resulting from the leakage of personal information and develops proposals for legal ensuring the information security of mobile phone users. The report first outlines the main actors, terms and concepts used in the report. Second the standards for mobile phone developers, although there is no guarantee of complete information security. In this case, the peculiarity of Russia is that standards used in the field of information security are voluntary. Third how law enforcement agencies protect the user community. In this case there is a potential danger that this may entail uncontrolled access of government agencies to confidential data.